ANALISIS CITRAAN PENGLIHATAN DALAM ANTOLOGI PUISI DI HADAPAN RAHASIA KARYA ADIMAS IMMANUEL - Leni Patmawati; Sumiharti Sumiharti; Sujoko Sujoko (Universitas Batanghari, 2018)
This research is intended to decribe imagery that is found in Poetry Anthology Di Hadapan Rahasia by Adimas Immanuel. The method of this research is descriptive by using content analysis. The sourec of the data is pramary and secondary data. In this research, the primary data is taken from the sequence of beutiful words that have a meaning and visual imagery in their every linein Poetry Anthology in Di Hadapan Rahasia by Adimas Immanuel. The secondary data is taken from books and literature. Based on the result of the research, it can be concluded that there are 30 imagery in the poetry written by Adimas Immanuel. The types of the imagery is follows: (1) 4 visual imagery. Thus, imagery is one of the way that can be used in identifying a poetry.Key words: imagery,poetryi,poetry anthology